Student's Problem-Solving Ability through the Realistic Mathematics Education with Fun Card - Windari, Puput; Winarti, Endang Retno (Department of Mathematics, Universitas Negeri Semarang, 2019)
The purpose of this study is to test: (1) classical mastery of problem-solving abilities in Realistic Mathematics Education Learning assisted with fun cards, (2) whether problem-solving abilities in Realistic Mathematics Education Learning Approach is better than learning with PBL, (3) the influence of students' learning responsibility towards problem-solving skills with the Realistic Mathematics Education approach, and (4) describe students' problem-solving abilities in terms of learning responsibility. This study uses a mixed method of sequential explanatory design, the population in this study was the seventh-grade students of one of Junior High School 36 Semarang the academic year of 2018/2019. The results showed that (1) students' problem-solving abilities through the Realistic Mathematics Education Learning Approach assisted with fun cards met classical learning completeness criteria, (2) problem-solving abilities of students who obtained Realistic Mathematics Education Learning assisted with fun cards are better than students who learn with Problem-Based Models Learning, (3) learning responsibilities have a positive effect on students' problem-solving skills in Realistic Mathematics Education Learning assisted with fun cards, (4) students' problem-solving abilities in terms of responsibility through the RME learning approach assisted with fun cards.